Triplet systemic therapy for hormone-sensitive prostate cancer: a critical review with a multidisciplinary approach - Almudena Zapatero; Teresa Alonso-Gordoa; Alfredo Rodríguez Antolín; Felipe Couñago; Felipe Couñago; Noelia Sanmamed; Mario Domínguez Esteban; Marta López Valcárcel; Ray Manneh; Ángel Borque-Fernando; Nuria Sala González; Pablo Maroto (Oncology Reviews)
This article aims to critically evaluate the evidence for triplet therapy consisting of androgen deprivation therapy (ADT), docetaxel and a second-generation androgen receptor pathway inhibitor ([ARPI]; abiraterone, enzalutamide, darolutamide or apalutamide) in patients with metastatic hormone-sensitive prostate cancer (mHSPC), and what this evidence reveals regarding the use of these treatments in clinical practice. A search of PubMed, Medline, Embase, Cochrane, Scopus and Web of Science was conducted in April 2024 to identify relevant prospective and retrospective observational trials, randomized controlled trials (RCTs) and meta-analyses. The search identified 52 relevant articles: six full articles and 31 abstracts based on three RCTs, one observational study and 14 meta-analyses. Abiraterone- or darolutamide-containing triplet therapy was significantly better than ADT + docetaxel for improving overall survival in all study populations, particularly subgroups with high-volume and/or synchronous disease. The tolerability of ADT + docetaxel and triplet therapy were similar with most adverse events related to docetaxel. There were no data comparing triplet therapy with ADT + ARPI doublet therapy. Triplet therapy appears to be the most effective first-line regimen for men with mHSPC, good performance status and high-volume and synchronous metastases. Darolutamide-based triplet therapy may also be of benefit in other patients with high- or low-risk disease. Careful consideration of the risks and benefits are required to determine which patients can be spared from receiving docetaxel and rather be treated with alternative regimens.